Pengaruh Pemanfaatan Teknologi Informasi dan Kompetensi SDM dalam Mendukung Efektivitas Sistem Informasi Akuntansi pada Lingkungan Bisnis Digital: (Studi Kasus pada PT. Pandowo Utomo Food Tahun 2024) - Farikhah; Nurdhiana; Triani (Jurnal Ilmiah Aset, 2026)
The development of the business world that has entered the era of globalization requires companies to increase the effectiveness of their resources. Including accounting information systems. Factors that can affect the effectiveness of accounting information systems are the utilization of information technology and the competence of human resources. This research aims to determine the effect of utilization of information technology and competence of human resources on the effectiveness of accounting information systems at PT. Pandowo Utomo Food Semarang in 2024. The sampling technique employed is the saturated sample method. The data analysis is conducted using Multiple Linear Regression. The collected data was processed using the Software Statistical Program for Science (SPSS) version 25 for windows. The results of this research indicate that the utilization of information technology and competence of human resources has a positive and significant effect on the effectiveness of accounting information systems.